Performance studies of HEFSM with 6 slot- 7 pole for HEV application - Ibrahim, Ismail Ishaq (2014)
Hybrid excitation machines (HEMs) that consist of permanent magnet (PM) and field excitation coil (FEC) as their main flux sources has several attractive features compared to interior permanent magnet synchronous machines (IPMSM) conventionally employed in hybrid electric vehicles (HEVs). Hybrid excitation flux switching machines (HEFSM) is one type of HEMs. This project is to decrease the PM size in a HEFSM so that the cost of the machine can be reduce. By reducing the size of PM, the torque and the power of the machine will be slightly different from the original PM size. The torque and other specification will be seen in the results.